Alternative Pathways of Cancer Cell Death by Rottlerin: Apoptosis versus Autophagy. (20th December 2012) - Torricelli, Claudia; Salvadori, Sara; Valacchi, Giuseppe; Souček, Karel; Slabáková, Eva; Muscettola, Michela; Volpi, Nila; Maioli, Emanuela
Abstract : Since the ability of cancer cells to evade apoptosis often limits the efficacy of radiotherapy and chemotherapy, autophagy is emerging as an alternative target to promote cell death. Therefore, we wondered whether Rottlerin, a natural polyphenolic compound with antiproliferative effects in several cell types, can induce cell death in MCF-7 breast cancer cells. The MCF-7 cell line is a good model of chemo/radio resistance, being both apoptosis and autophagy resistant, due to deletion of caspase 3 gene, high expression of the antiapoptotic protein Bcl-2, and low expression of the autophagic Beclin-1 protein. The contribution of autophagy and apoptosis to the cytotoxic effects of Rottlerin was examined by light, fluorescence, and electron microscopic examination and by western blotting analysis of apoptotic and autophagic markers. By comparing caspases-3-deficient (MCF-7 3def ) and caspases-3-transfected MCF-7 cells (MCF-7 3trans ), we found that Rottlerin induced a noncanonical, Bcl-2-, Beclin 1-, Akt-, and ERK-independent autophagic death in the former- and the caspases-mediated apoptosis in the latter, in not starved conditions and in the absence of any other treatment. These findings suggest that Rottlerin could be cytotoxic for different cancer cell types, both apoptosis competent and apoptosis resistant.